Do macroeconomic factors affect the credit risk of islamic banks? evidence from Malaysia - Safeza Mohd Sapian; Mansur Masih (MPRA, 2024)
This paper makes an attempt to investigate whether the macroeconomic factors contribute to the credit risk exposure and non-performing financing (NPF) of Islamic banks. Malaysia is taken as a case study. The standard time series techniques are used to analyze the issue. The variables that have been chosen for the study are gross domestic product (GDP), Non-Performing Financing rate, Islamic financing rate (IFR) and unemployment rate (UMPT). The findings tend to indicate that Islamic Financing rate (IFR) stands out as the only factor that had a significant impact on the credit risk exposure and non-performing financing as well as the performance of Islamic banks in the context of Malaysia.